2018
DOI: 10.12705/671.10
|View full text |Cite
|
Sign up to set email alerts
|

Large–scale digitization of herbarium specimens: Development and usage of an automated, high–throughput conveyor system

Abstract: The billions of specimens housed in natural science collections provide a tremendous source of under–utilized data that are useful for scientific research, conservation, commerce, and education. Digitization and mobilization of specimen data and images promises to greatly accelerate their utilization. While digitization of natural science collection specimens has been occurring for decades, the vast majority of specimens remain un–digitized. If the digitization task is to be completed in the near future, innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 50 publications
1
28
0
4
Order By: Relevance
“…) showed that the genetic variation of the samples is organized into seven groups, which correspond to traditionally well‐established species. These species were recovered as being monophyletic according to the AFLP data treated with phenetic reconstruction methods, which is consistent with findings by Gutiérrez‐Larruscain et al () based on phylogenetic reconstructions using DNA sequence data.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…) showed that the genetic variation of the samples is organized into seven groups, which correspond to traditionally well‐established species. These species were recovered as being monophyletic according to the AFLP data treated with phenetic reconstruction methods, which is consistent with findings by Gutiérrez‐Larruscain et al () based on phylogenetic reconstructions using DNA sequence data.…”
Section: Discussionsupporting
confidence: 89%
“…et al The species P. aschersonianum and P. verbascifolium belong to a complex of species distributed in the Balkan Peninsula and Anatolia, and are characterized by a lanate indument that gives them an ashen appearance. In the reconstruction presented in Gutiérrez‐Larruscain et al (), this species was recovered in a basal position within the Pentanema montanum clade as a sister group to the rest of the species included within this clade, which are characterized as being endemic to the western Mediterranean area. In the case of Pentanema langeanum , endemic to the C and N of the Iberian Peninsula, the taxonomic status of this species has been controversial due to its morphological similarity with P. conyzae , since both have short ray florets.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Nomenclature and distribution updates according to Meve and Liede (2002), Barbaro and Kreutz (2007), Crespo et al (2015), Ardenghi and Polani (2016), Wilson (2016), Lazzeri (2017), Banfi (2018), Baum and Johnson (2018), Di Gristina et al (2018), Gutiérrez-Larruscain et al (2018), Nardi et al (2018), Madhani et al (2018), Selvaggi et al (2018) and corrections to Bartolucci et al (2018) are provided in Supplementary material 1. F. Bartolucci…”
Section: Floristic Recordsmentioning
confidence: 99%